BENTUK DAN FUNGSI TARI SILAMPARI KAYANGAN TINGGI DI LUBUKLINGGAU SUMATRA SELATAN - Hilaria Widia Ayuningtyas; Syahrial Syahrial (Institut Seni Indonesia Surakarta, 2020)
This study examines Silampari Kayangan Tinggi dance in Lubuklinggau. Its main focus is on the aspects of form and function in its prsentation. Using the theory of form by Suzanne K. Langer which is described using concept of Y. Sumandiyo Hadi and theory of function by M. Jazuli. This research is a type of qualitative research with an intersubjective approach that emphasize observation in the field by capturing information and illustrated in fact. This dance form is also a development of the Silampari dance which is the root of the welcoming dance in Lubuklinggau city and Musi Rawas district. This dance ia a guest welcoming dance perfomed by woman totaling four to ten dancers and two tepak bearers namely Bujang Dere (son and daughter of the city of Lubuklinggau). The result of this study indicate that the Silampari Kayangan Tinggi dance as form of respect to the guest of honor who visited Lubuklinggau.Keywords: Form, Function, Silampari Kayangan Tinggi Dance.